سبل إرساء السياحة الزراعية من خلال - دراسة حالة برنامج "أرياف" بالمدينة المنورة - - دويدي, خديجة هاجر (جامعة الوادي - University of Eloued, 2022)
تنبهنا الأزمة الصحية الحالية لكوفيد – 19 لأهمية السياحة الداخلية، والتي أصبحت في مقدمة الحلول، وتأتي هنا السياحة الزراعية كأحد مكوناتها ؛ لكن مفهوم "السياحة الزراعية" غير معروف كثيرا ولا مقنن في عديد من الدول، على رأسها الجزائر. الأمر الذي دعانا للبحث في هذه الورقة عن واقع هيكلة وتشكيل السياحة الزراعية في المملكة العربية السعودية، من خلال دراسة برنامج "أرياف" في المدينة المنورة، في محاولة للاستفادة من حيثيات هيكلة نشاطه، لمحاكات نموذجه في الجزائر. وقد بينت نتائج البحث أن السياحة الزراعية لبرنامج "أرياف" تخضع لعدد من الدعائم الثابتة : مثل الهيئات المؤولة عنه والمشاركة فيها، وأنواع المعايير التي يجب أن تتوفر في المزارع، و ربط البرنامج بأهداف التنمية المستدامة. The current health crisis of Covid-19 alerts us to the importance of domestic tourism, which has become at the forefront of solutions, and agricultural tourism comes here as one of its components; But the concept of "agri-tourism" is not very well known and is not codified in many countries, especially Algeria. Which prompted us to discuss in this paper the reality of structuring and shaping agricultural tourism in the Kingdom of Saudi Arabia, by studying the “Aryaf” program in Medina, in an attempt to benefit from the rationale for structuring its activity, to emulate its model in Algeria. The results of the research showed that agro-tourism for the "Aryaf" program is subject to a number of fixed pillars: such as the bodies responsible for it and participation in it, the types of standards that must be met on farms, and linking the program to the goals of sustainable development.
Ways to establish agricultural tourism through A case study of the "Aryaf" program in Madinah
مقال
Keywords: السياحة الزراعية ; السياحة الزراعية السعودية ; التنمية المستدامة ; برنامج أرياف